Animal writing : storytelling, selfhood and the limits of empathy - Sands, Danielle (Crosscurrents (Edinburgh University Press), 2019)
"Combining recent insights from animal studies, critical plant studies and the new materialisms, Danielle Sands reads fiction and philosophy alongside each other to propose a method of thinking of and with animals that draws on a bestiary of affects. She challenges the claim that empathy should be the primary mode of engagement with nonhuman life. Instead, she looks at the stories that we tell, and are told, by insects - beings at the edges of animal life. The indifference, even disgust, that these creatures evoke in us forms the basis for a new ethics not limited by empathy."--